Statistical optimization of physichochemical factors for protease production by Bacillus licheniformis on skim latex serum effluent fortified media - Mardina, V.; Yusof, Faridah; Alam, Md Zahangir (School of Engineering. Taylor’s University, 2015)
In this study Response Surface Methodology has been applied to optimize the physicochemical factors in maximizing the production of protease by Bacillus licheniformis in a medium fortified with skim latex serum. The results showed that the production increased approximately a nine fold to the original medium. The predicted values of the model were in agreement with the experimental values and validation steps verify its adequacy and accuracy. Thus, this study presents a holistic approach for the bioconversion of agro-industries waste to value-added protease enzyme, potentially useful in many industries and thus minimizing the release of polluted water into the environment by the natural rubber industries.